PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1940)
Abstract The problems mentioned in the paper were prepared by the Board of Examiners of the American Institute of Accountants and were presented as the first half of the May 1940 C.P.A. examination in those states using the Institute questions. The candidates were allowed six hours to solve the five problems. A detailed list of problems is mentioned in the paper.